Can historians order off the menu?: - Koby Song-Nichols (Canadian Food Studies, 2024)
While historians have used menus to tell part of the histories of restaurants, little guidance has been provided on how we should approach these unique culinary documents. This lack of instruction becomes more apparent in light of the impressive amount of archival work and digitization of historical menus done in recent years. As a response, this article presents a method that I have developed for analyzing menus. Drawing on interdisciplinary perspectives as well as experience teaching and researching with menus, this method recognizes menus as documents that can reveal the many relationships and connections intersecting in, flowing through, and making up restaurants. This method is divided into four steps: 1) (Un)Identifiable details; 2) Logics/story; 3) Mess or Marginalia; and 4) Cross-Menu comparison. By moving the reader through the method and offering an example of historical menu analysis, this article demonstrates some of the many historical insights that emerge through careful consideration of these sources.